Prototype Mobile Application Menggunakan Metode Five Planes Pada Startup Mainheal - I Kadek Setiawan; A.A. Istri Ita Paramitha; Tiawan Tiawan (Institut Bakti Nusantara, 2023)
In Indonesia, the mental health condition of the community is currently one of the problems that has received less attention. The number of people suffering from mental disorders continues to increase. There are around 236 million people in Indonesia who suffer from mental disorders. On average, people affected by mental and mental disorders feel embarrassed to go to psychology because they want to maintain privacy and images in the community. This opportunity can also be utilized by people engaged in startups. Mainheal is here to answer all these problems to provide psychological health consultation services with psychologists or people who are experts in their fields online or online. In designing the prototype mobile application startup Mainheal uses the Five Planes method because the five planes method already has a framework that is ready to be used in the development of user experience that is flexible and can be adapted to the development of an application. this method consists of 5 stages, namely, strategy plane, scope plane, structure plane, skeleton plane, surface plane and coupled with an evaluation to validate the design that has been made.